2011
DOI: 10.1097/inf.0b013e3182093814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Prepregnancy Pertussis Booster Dose on Maternal Antibody Titers in Young Infants

Abstract: To examine the influence of a pertussis booster vaccination on the transfer of maternal antibodies, 24 nonpregnant women received a tetanus, diphtheria, acellular pertussis booster vaccine between 2 consecutive pregnancies. Blood was drawn from mothers and off-spring. Efficient transplacental antibody transfer and significantly higher antibody titers against 3 pertussis antigens were observed in cord blood and in blood of 1-month-old infants born after a maternal booster vaccination compared with results in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 10 publications
0
42
0
2
Order By: Relevance
“…30 A fines de 2011, el ProNaCEI convocó a la Comisión Nacional de Inmunizaciones y se analizó esta estrategia: la Argentina fue el primer país de Latinoamérica en recomendar la vacuna dTpa para las embarazadas con el objetivo de disminuir la mortalidad en lactantes menores de un año. 31 E l f o r t a l e c i m i e n t o d e l a v i g i l a n c i a epidemiológica y las estrategias de vacunación implementadas 32,33 se contraponen al mayor número de casos y fallecimientos, sobre todo visualizando que las coberturas de vacunación del lactante y del ingreso escolar se mantuvieron estables en el período estudiado y en valores superiores al 80%.…”
Section: Discussionunclassified
“…30 A fines de 2011, el ProNaCEI convocó a la Comisión Nacional de Inmunizaciones y se analizó esta estrategia: la Argentina fue el primer país de Latinoamérica en recomendar la vacuna dTpa para las embarazadas con el objetivo de disminuir la mortalidad en lactantes menores de un año. 31 E l f o r t a l e c i m i e n t o d e l a v i g i l a n c i a epidemiológica y las estrategias de vacunación implementadas 32,33 se contraponen al mayor número de casos y fallecimientos, sobre todo visualizando que las coberturas de vacunación del lactante y del ingreso escolar se mantuvieron estables en el período estudiado y en valores superiores al 80%.…”
Section: Discussionunclassified
“…Moreover, some studies also showed a rapid reduction in antibody levels in children whose mothers received a booster dose in the pre-conception period or in the initial 2-3 months of pregnancy; their antibody levels were presumably inadequate for ensuring protection against pertussis. 110,111 Immunization during pregnancy has not been taken into serious consideration for some time since it is difficult to verify its efficacy and safety. Recently this possibility has been reconsidered, since the rationale for this strategy is well known and it plays a key role in the prevention of other neonatal diseases, including tetanus and influenza.…”
Section: Strategies For the Prevention Of Pertussismentioning
confidence: 99%
“…25,[28][29][30] Los anticuerpos transferidos al neonato durarían aproximadamente 2 meses, momento en que se iniciaría el esquema habitual de vacunas. 34,35 La falta de datos sobre eficacia clínica y la posible interferencia con las vacunas posteriores han sido motivo de preocupación. El estudio de Heinenger reporta menor respuesta serológica al esquema habitual de vacunación cuando se utilizan vacunas celulares.…”
Section: Figura 3 Comparación De Los Títulos De Anticuerpos Anti-borunclassified